The Growth of Epicotyl Shoots of Glutinous Corn (Zea mays L. var. ceratina) on Murashige Skoog Medium with NAA and Coconut Water - Delviera, Dhea Amanda; Zakiah, Zulfa; Turnip, Masnur (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Glutinous corn (Zea mays L. var. ceratina) is a local variety known for its distinctive traits, particularly its high amylopectin content, comprising 72% amylopectin and 28% amylose. This research aims to explore the impact of incorporating Naphthalene Acetic Acid (N.A.A.) and coconut water and identify the optimal concentrations that influence the growth of epicotyl shoots in glutinous corn. The study was conductedk in the Tissue Culture Laboratory at the Department of Biology, Faculty of Mathematics and Natural Sciences, Tanjungpura University in Pontianak. A completely randomized design (C.R.D) with factorial arrangements was employed. The first factor considered various concentrations of NAA (0, 0.5, 1.0, and 1.5 ppm), while the second factor involved coconut water at different concentrations (0%, 15%, 30%, and 60%). The findings indicated that the combination of NAA and coconut water significantly impacted the shoot emergence time and height. The combinations of 0.5 ppm NAA with 15% and 30% coconut water resulted in the fastest shoot growth, averaging 2.4 days after seed treatment (hst). In contrast, using 30% coconut water alone, without NAA, produced the tallest shoots, averaging 3.48 cm. However, the growth of glutinous corn epicotyl shoots was optimal only until 14 days of age.